Differential response of natural regeneration to silvopastoral use intensity in mixed forests of northern Patagonia, Argentina - Arpigiani, Daniela F.; Chillo, María Verónica; Soler Esteban, Rosina Matilde; Amoroso, Mariano M. (Elsevier, 2022)
Silvopastoral use (combined livestock and forestry) is widely distributed in South America’s native forests. Without medium to long-term planning, this activity may affect the population dynamics of the dominant canopy tree species, resulting in forest degradation. The early stages of tree life cycles are usually the most vulnerable, so the successful establishment and development of seedlings and saplings is a key indicator of the potential forcontinuity of the tree layer over time. This study evaluated the effect of silvopastoral use intensity (SUI) upon the density and development of dominant tree species - Austrocedrus chilensis and Nothofagus dombeyi - along a gradient generated by spatially and temporally heterogeneous livestock activity and forest harvesting in mixed forests of northwestern Patagonia, Argentina. We monitored the survival and growth of 740 seedlings and saplings over two years (2018–2020) in three medium-sized estates SUI gradients and upland migration of livestock during the summer season. We also evaluated changes in biophysical variables that influence the tree regeneration process: light input, soil moisture, and understory vegetation structure. We found that higher SUI modifies the biophysical environment, increasing light input and horizontal understory cover. The response of saplings and seedlings to SUI was not homogenous; N. dombeyi showed significant changes in its regeneration dynamics, denoted by a decrease in the density of seedlings and an increase in the density and height growth of the saplings along the SUI gradient. Meanwhile, A. chilensis only showed tendencies to deformation by browsing (height: diameter ratio). Thus, in medium-size estates with low stocking rates and which are free of herbivory during summers; fast-growing species (e.g. N. dombeyi) could be favored by the slight canopy openings, compensating for the negative impact of browsing. However, it is necessary to monitor and potentially individually protect A. chilensis saplings until browsing height is exceeded.